Intersetorialidade na saúde: estratégia de atuação do Serviço Social - Silva, Gilvaneide Nunes da (2013)
This study had the purpose to present the research results about political field of intersectorial of the social health, having as reference the social workers inserted in the health service, specially, the emergency care from a average complexity hospital in Paraíba while participant of a interdisciplinary team to ensure the health rights in the perspective of intersectionality and assistance integrity. The methodological procedure used, apart from the bibliographic research, was made a exploratory nature research with social workers, taking in consideration the little exploration of the thematic, above all what terms the intersectorial, agenda has been made by authors from diverted areas of knowledge which, on the other hand, treat the thematic in different ways, particularly in complementary sectors about the population need. As practice and network work. There are other authors also that treat the building of the intersectorial process. Learns that in the political social field, specially the health it‘s agenda bring the necessity to intersectionality. We sought in this matter understand how the professionals of social workers from the emergency care from HPMGER identify and act with the intersectoriality to bring the integrity, as well how to identify and analyze the existence of intersectorials actions developed by the social workers to enable the health users to its full power. In the political area formation falls on to the health service where the social workers act. The empirical research results show the convergent and diverts elements about the comprehension and the social worker relation with the intersectoriality, building from perceptions of transverse relations from professionals executors of users rights, =part from that, shows that the intersectorial concretion, yet still a robust challenge. The research subjects analyze that still didn‘t have the channel consolidation that enable the intersectoriality because do not have a public policy management planning with the three levels and beyond, whether intersectoral planning. Infer further that the construction of intersectoral bumps up, mostly in bureaucratization of services, relationships marked by disputes in professional fields, especially by clientelistic and patrimonial culture that permeates health policy. At the same time, the results show that in the exercise of professional social workers, although they do not recognize that perform intersectoral actions, there is the presence of intersectoral actions since the professional services mobilize various sectors so that users are met. Thus, it is assumed that the discussion will furthermore because we wanted to uncover which of the limits and challenges that interposes practicing social worker, seeking to uncover how social service professionals from PA and HPMGER it is identified and articulated as being referrals within the health and raise the debate in the fabric of intersectoral arrangements posts from social relations, professional, institutional policies that underlie social, especially health, aiming to contribute to the guarantee of social rights to SUS users. Therefore, we can then conclude from the investigated fact that intersectionality is of an immense challenge, because for users to access integral health services it will need a change in vision not only of the executors of social policies, especially health, but especially the formulators of public policy in all levels of management.